Informed consent to legal treatment – lessons from medical informed consent. Issue 2 (4th May 2017) - Katvan, Eyal; Shnoor, Boaz
ABSTRACT: Lawyers are their clients' representatives, and therefore, they are expected to follow their clients' wishes. On the other hand, in order to best serve their clients' interests, they are supposed to act according to their best professional judgement. These two duties sometimes conflict. In this article, we use empirical and theoretical methods, comparing Israeli and American law, and relying on lessons from the medical profession, to investigate the limits of the lawyer's duties to find out her client's wishes, to seek the client's approval to the lawyer's actions, and to inform her client about future actions and about development in the case. The results of a lawyers' survey and a clients' survey that we conducted show that clients wish to be more involved in their cases than they currently are: they wish that lawyers would give them more information about the case and more frequently ask for their consent. Moreover, we show that theoretical arguments favor such an approach, and that this approach is the law in the medical profession. However, analyzing Israeli and US jurisprudence, it seems that the law is willing only to indicate an overall, non-specific duty to inform, but leaves the decision power with the lawyers. We therefore call for legal reform.